FINITE INTEGRAL FORMULA INVOLVING ALEPH-FUNCTION AND GENERALIZED MITTAG-LEFFLER FUNCTION - D. Kumar; F. Y. Ayant; A. Singh; P. K. Banerji (Проблемы анализа, 2020)
The aim of this paper is to establish general definite integrals involving product of the Aleph function and the generalized Mittag-Leffler function with general arguments. This integral yields a number of known results as special cases. For the sake of illustration, several corollaries are also presented as special case of our main results.